2015
DOI: 10.3892/ijo.2015.3030
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent expression and subcellular localization of the tight junction protein claudin-4 in HEC-1A endometrial cancer cells

Abstract: Abstract. Endometrial cancer is the most common female reproductive cancer in the United States and is associated with deregulated tight junction protein expression. Given the highly estrogen-responsive nature of this tissue, we investigated the effects of estrogen and its agonist, 4-OH TAM, on the expression and subcellular localization of the tight junction protein claudin-4 (CLDN-4), in HEC-1A endometrial cancer cells. In untreated HEC-1A cells, we observed dramatic overexpression of claudin-4 protein. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…Moreover, claudin-2 was observed in the nucleus in human lung adenocarcinoma cells [83], and claudin-3 was reported to be present in nuclei in breast cancer cell lines [84] and human colorectal cancer [85]. Changes in claudin-4 location in endometrial cancer cells were also observed [86]. Interestingly, relocation of claudin-1 is not associated with protein modification, based on not-observed changes in the mass of this protein [80], whereas claudin-2 was reported to be dephosphorylated when located in nuclei of cells [83].…”
Section: Localization Of Claudins In Cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, claudin-2 was observed in the nucleus in human lung adenocarcinoma cells [83], and claudin-3 was reported to be present in nuclei in breast cancer cell lines [84] and human colorectal cancer [85]. Changes in claudin-4 location in endometrial cancer cells were also observed [86]. Interestingly, relocation of claudin-1 is not associated with protein modification, based on not-observed changes in the mass of this protein [80], whereas claudin-2 was reported to be dephosphorylated when located in nuclei of cells [83].…”
Section: Localization Of Claudins In Cellsmentioning
confidence: 86%
“…Cuevas et al showed that claudin-4 expression in HEC-1A cells exposed to physiological concentrations of estradiol (100 nM) was modulated, and its localization was changed. Cells without hormonal treatment presented most of the claudin-4 localization in cytoplasm and membrane, whereas 50 nM of estradiol caused an increase in the expression and membrane localization [86]. Claudin-11 is known to be regulated hormonally, and its knockout models result in infertility [87].…”
Section: Hormonal Regulation Of Claudinsmentioning
confidence: 99%
“…Nuclear localization has been reported for ZO1/ZO2 [69,70] and CLDN1-4 [71][72][73][74] in several types of cancer cells. The conditions or inducers under which these TJ proteins localize in the nucleus are poorly understood.…”
Section: Non-junctional Localization Of Tight Junction Proteinsmentioning
confidence: 97%
“…They might serve as a claudin pool for tight junction protein recycling [70] or being part of the cellular interface to the extracellular matrix [14,36]. Also nuclear localization was reported for claudin 1, 2, 3 and 4 especially in tumour cells [11,24,34,65] suggesting that claudins may act as modulators of gene transcription, cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%